MODEL KOLABORASI PEMERINTAH DAERAH DENGAN PERUSAHAAN LISTRIK NEGARA DAN PEMBANGKIT LISTRIK TENAGA BIOGAS DALAM MEMANFAATKAN ENERGI BARU TERBARUKAN - Achmad; Aries Djaenuri; Tjahya Supriyatna; Muchlis Hamdi (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
This research aims to analyze the collaboration policy of the Regional Government with the State Electricity Company and Biogas Power Plant in utilizing renewable energy. This research was conducted in Rantau Sakti Village, North Tambusai District, Rokan Hulu Regency, Riau Province using a qualitative approach. Data collection techniques used in this study in the form of interviews, observation and documentation studies. The results of the study found that the collaboration of the Regional Government with the State Electricity Company and the Biogas Power Plant in utilizing new and renewable energy is basically not yet created and formed intactly and comprehensively because based on the facts only indicates that there is a potential collaboration of the Regional Government with the State Electricity Company and Biogas Power Plant. If the Biogas Power Plant already has legality and clarity on the legal status and its management as a result of a change in the Regional Government Law which causes the authority in the energy sector to be drawn to the provincial level, the Regional Government of Rokan Hulu Regency loses management rights over the Power Plant Biogas.